1996
DOI: 10.1007/bf00127097
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of adsorption of liquid mixtures of N2 and O2 in a model faujasite cavity at 77.5 K

Abstract: Grand canonical Monte Carlo simulations of adsorption of N 2 and 02 and their mixtures in a model zeolitic cavity 14 A in diameter were performed at 77.5 K for pressures ranging from zero up to saturation, where the adsorbed phase is in equilibrium with coexisting vapor and liquid phases. The same intermolecular potential functions were employed for gas-gas interactions in the vapor, liquid, and adsorbed phases. The gas-solid interaction potential includes dispersion-repulsion energy, induced electrostatic ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…This was explained with a partial exclusion of the larger molecules from portions of the micropore volume. A negative deviation from Raoult's law in the adsorbed mixture was also found in a simulation of adsorption of liquid N 2 and O 2 in a model NaX zeolite cavity at 77.5 K …”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…This was explained with a partial exclusion of the larger molecules from portions of the micropore volume. A negative deviation from Raoult's law in the adsorbed mixture was also found in a simulation of adsorption of liquid N 2 and O 2 in a model NaX zeolite cavity at 77.5 K …”
Section: Introductionsupporting
confidence: 61%
“…This was explained with a partial exclusion of the larger molecules from portions of the micropore volume. A negative deviation from Raoult's law in the adsorbed mixture was also found in a simulation of adsorption of liquid N 2 and O 2 in a model NaX zeolite cavity at 77.5 K. 16 Adsorption of an equimolar gas mixture of nitrogen and methane in zeolite Y was studied by Maddox and Rowlinson, 17 who used a two-site LJ model for nitrogen and a five-site LJ model for methane. They found that methane is adsorbed preferentially and that selectivity was almost independent of the pressure.…”
Section: Introductionmentioning
confidence: 76%
“…Molecular simulation offers an attractive means to investigate siting and segregation effects in molecular sieves because a single simulation can yield both the macroscopic adsorption thermodynamics and the microscopic siting of the molecules. Adsorption isotherms and heats of adsorption have been calculated for a variety of systems using grand canonical Monte Carlo (GCMC) simulations. Many of these studies have focused on silicalite, which has a set of straight channels intersected by a set of zigzag channels. Several groups have seen that small molecules, such as methane or xenon, prefer the channels over the intersections. , June et al found that at low loading linear alkanes adsorb in the channels but branched alkanes prefer the roomier channel intersections.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling phase behavior of fluids at interfaces is necessary to understand molecular mechanisms of surface tension in liquids and adsorption behavior at surfaces and interfaces. , Important features of interfaces include density gradients and oscillatory density profiles near the surfaces of liquids and the interrelationship between two- and three-dimensional behaviors. The role of dimensionality is not limited to geometry of the system but also includes correlation effects on heterogeneous surfaces , and in nanopores. Dimensionality also affects critical phenomena including long-range critical fluctuations and universal scaling laws…”
Section: Introductionmentioning
confidence: 99%